2019
DOI: 10.1111/mpp.12790
|View full text |Cite
|
Sign up to set email alerts
|

Plasmopara viticola effector PvRXLR131 suppresses plant immunity by targeting plant receptor‐like kinase inhibitor BKI1

Abstract: Summary The grapevine downy mildew pathogen Plasmopara viticola secretes a set of RXLR effectors (PvRXLRs) to overcome host immunity and facilitate infection, but how these effectors function is unclear. Here, the biological function of PvRXLR131 was investigated via heterologous expression. Constitutive expression of PvRXLR131 in Colletotrichum gloeosporioides significantly enhanced its pathogenicity on grapevine leaves. Constitutive expression of PvRXLR131 in Arabidopsis promoted Pseudomonas syringae DC3000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 72 publications
(103 reference statements)
0
33
0
Order By: Relevance
“…, 2017; Lan et al . , 2019). Because CfEC92 functions in host cells, our next work will focus on seeking the possible targets of CfEC92 in apple leaf cells in order to elucidate the molecular basis underlying plant defence suppression.…”
Section: Discussionmentioning
confidence: 99%
“…, 2017; Lan et al . , 2019). Because CfEC92 functions in host cells, our next work will focus on seeking the possible targets of CfEC92 in apple leaf cells in order to elucidate the molecular basis underlying plant defence suppression.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, 83 PvRXLR effectors, cloned from a Chinese P. viticola isolate, were characterized based on subcellular location and the ability to suppress cell death induced by two elicitors, INF1 and Bax (Liu et al, 2018). Many PvRXLR effectors were found to be able to suppress plant immunity, and of these PvRXLR131 was further shown to suppress plant immunity by targeting BKI1 (Lan et al, 2019). Meanwhile, several PvRXLRs were shown to induce cell death when expressed in Nicotiana benthamiana (Liu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Infection of P. viticola 'JL-7-2ʹ was performed according to previous studies. 20,24 The susceptible grapevine (V. vinifera 'Thompson Seedless') leaf discs were inoculated with 30 µL spore suspension with a final concentration of 1 × 10 5 spores/mL on the abaxial side, and then incubated in an incubator (18ºC, 11 h light/13 h dark, 66% relative humidity). Phenotypic monitoring and sampling for RNA extraction were performed at indicated times.…”
Section: Pathogen Infection Assaymentioning
confidence: 99%
“…23 Our recent studies revealed that PvRXLR131 suppresses host resistance by targeting BRI1 kinase inhibitor 1. 24 In this study, we characterized the role of PvRXLR159 in plant-microbe interaction.…”
Section: Introductionmentioning
confidence: 99%